Cover Feature: Effect of Experimental Operations on the Limiting Current Density of Oxygen Reduction Reaction Evaluated by Rotating‐Disk Electrode (ChemElectroChem 5/2020). Issue 5 (21st February 2020) - Zhong, Guoyu; Xu, Shurui; Liu, Lei; Zheng, Cheng Zhi; Dou, Jingjing; Wang, Fengye; Fu, Xiaobo; Liao, Wenbo; Wang, Hongjuan
Abstract : The Cover Feature illustrates the effect of catalyst loading, O2 inlet conditions, and electrolyte viscosity on the steady‐state limiting current density ( I lim ) for the oxygen reduction reaction. The catalyst loading and O2 inlet conditions are the critical factors for obtaining the correct I lim value. The correct limiting currents and high‐quality linear voltammetry scan curves could be obtained with suitable experimental operation. More information can be found in the Article by G. Zhong et al. on page 1107 in Issue 5, 2020 (DOI: 10.1002/celc.201902085 ).